Features of detecting acousto-electromagnetic information leakage channels - Oleynikov, A.M.; Lykov, Yu.V.; Pavlenko, Y.S. (Radiotekhnika, 2025)
The article highlights the features of the formation and detection of acousto-electromagnetic information leakage channels caused by acousto-electric transformations in technical devices. These channels present a significant threat to information security, as they convert acoustic oscillations into electrical or electromagnetic signals that may carry confidential information. The primary focus is on the classification of acousto-electric and acousto-magnetic channels, which are divided into direct and modulation channels. Direct channels arise from the direct interaction of acoustic waves with sensitive device elements, such as piezoelectric elements, speakers, or transformers. Modulation channels are formed when acoustic influence changes the parameters of high-frequency generator signals, creating hazardous modulations. The physical processes underlying acousto-electric and acousto-magnetic transformations are examined. Acoustic waves alter the electrical parameters of sensitive elements such as inductance, capacitance, or electromagnetic permeability. This leads to the generation of signals that can be detected in power networks or transmission lines. The article describes methods for detecting acousto-electromagnetic channels. For direct channels, a setup including an acoustic generator, a sound wave emitter, and a spectrum analyzer that records output electrical signals is used. For modulation channels, an analysis of high-frequency signals modulated by acoustic waves is applied. A comprehensive set of measures to neutralize acousto-electromagnetic channels is proposed. These measures include shielding technical devices to protect against acoustic waves, using noise-absorbing materials, optimizing device designs to reduce their sensitivity to acoustic influences, and monitoring the acoustic environment using spectrum analyzers. Masking signals in rooms with high-security requirements are also an effective measure.